THE APPLICATION OF ELECTROMEDICAL TECHNOLOGY IN MODERN HEALTHCARE SYSTEMS: CHALLENGES AND OPPORTUNITIES - Permana Yoga Utama, Yuris (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Electromedical technology has transformed modern healthcare by enabling precise diagnostic and therapeutic tools, reducing errors, and improving patient outcomes. This paper explores the integration of electromedical devices within healthcare systems, focusing on the challenges and opportunities these technologies present. While advancements have optimized patient monitoring, treatment personalization, and medical data collection, there are still barriers to widespread adoption, including cost, regulatory compliance, and training requirements. The study investigates the current use of electromedical technology in various healthcare settings, examining case studies that highlight both its benefits and limitations. Through an in-depth review of literature and real-world applications, this research aims to offer insights into how electromedical advancements are shaping the future of healthcare. Recommendations for enhancing accessibility, safety, and efficiency of electromedical technology are also discussed, emphasizing the potential for these innovations to bridge gaps in care delivery.